Prevalence of smoking, alcohol consumption, and drug abuse in Iranian adults: Results of Azar Cohort Study - Sahar Naghizadeh; Elnaz Faramarzi; Hossein Akbari; Nasrin Jafari; Parvin Sarbakhsh; Asghar Mohammadpoorasl (Tabriz University of Medical Sciences, 2023)
Background: Substance abuse has significant health impacts on families and society as a whole. We aimed to provide detailed prevalence estimates of substance abuse among the Azar Cohort Study respondents in Tabriz, Iran. Methods: Data on 15006 participants of Azar Cohort Study were analyzed. The variables included tobacco smoking, alcohol use, drug abuse, and socio-demographic characteristics. The prevalence of substance abuse (with a 95% confidence interval) was calculated using the direct standardization method. Results: Overall, 9.3% and 6.2% of the participants were regular and heavy cigarette smokers, respectively. Also, 1.9% and 2.1% of participants reported a history of using illicit drugs and alcohol, respectively. Substance abuse was more prevalent among males than females. Substance abuse varied significantly with age and socioeconomic variables. Conclusion: We identified specific demographic and socioeconomic groups with a higher prevalence of all studied behaviors. Such high-risk groups should be targeted when designing substance abuse prevention programs.